The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Sancar, U.; Lericolais, G.; Menot, G.; Bard, E. (Marine Geology, 2007)
High-resolution seismic reflection profiles and analyses of the sedimentary substrate at the Sea of Marmara (SoM) entrance to the Strait of Istanbul (Sol, Bosphorus) provide a detailed record of the transgression that took place after the SoM reconnected with the Mediterranean. The sediments progressively fill a paleo shelf valley that incised the margin from the Sol to the shelf break at the time of the pre-Holocene lowstand. We map seven seismic reflection units that can be confidently correlated to sediment cores by lithology and physical properties. Sediments in the cores are dated by radiocarbon methods. Early channel and levee deposits within the paleo valley belong to the Younger Dryas cold stage and record outflow from the Black Sea via the Sol. Small clinoform packages on the valley margin formed in proximity to climbing paleo shorelines. The elevations of these deposits conform to the sealevel history recorded in Barbados corals. The younger part of the succession includes a subaqueous prodelta sourced from the Kurbagalidere River. Its relatively young age when the Holocene sea had almost reached its modem level suggests that the thick progradational and aggradational clinoform development was primarily a response to sediment supply rather than the filling of expanding accommodation space. Our findings refute the hypothesis of Aksu et al. (Aksu, A.E., Hiscott, R.N., Mudie., P.J., Rochon, A., Kaminski, M.A., Abrojano, T., Yasar, D., 2002a. Persistent Holocene outflow fromn the Black Sea to the Eastern Mediterranean contradicts Noah's Flood hypothesis, GSA Today 10,(6), 3-7., Aksu, A.E., Hiscott, R.N., Kaminski, M.A., Mudie, P.J., Gillespie, H., Abrojano, T., Yasar, D., 2002b. Last glacial-Holocene paleoceanography of the Black Sea and Marmara Sea: stable isotopic, foraminiferal and coccolith evidence. Mar. Geol., 190, 119-149.) and Hiscott et al. (Hiscott, R.N., Aksu, A.E., Yasar, D., Kaminski, M.A., Mudie, P.J., Kostylev, V.E., MacDonald, J.C. Isler, F.I., Lord, A.R., 2002. Deltas south of the Bosphorus Strait record persistent Black Sea outflow to the Marmara Sea since similar to 10 ka, Mar. Geol., 190,95-118., Hiscott, R.N., Aksu, A.E., Mudie., P.J., Kaminski, M.A., Abrajano, T, Yasar, D., Rochon, A., 2007. The Marmara Sea gateway since similar to 16 ky BP: non-catastrophic causes of paleoceanographic events in the Black Sea at 8.4 and 7.15 ky BR In Yanko-Hombach,V, Gilbert, A.S., Dolukhanov, P.M. (Eds.), The Black Sea Flood Question, Springer, The Netherlands, 89-117.) that this deposit was supplied from the Sol and that its presence requires a persistent Black Sea outflow since 10 C-14 ka bp (not corrected from the reservoir age or calibrated). (c) 2007 Elsevier B.V All rights reserved.
210tuTimes Cited:36Cited References Count:52